Edith Stein's Ontology - A Phenomenological Approach - Kluck, Steffen (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2016)
Starting from a critique of Husserl’s and Heidegger’s understanding of phenomena, the presented paper undertakes systematically orientated productive approachto some motifs of Stein’s ontology. It is possible to highlight four meaningful points of contact for the presented phenomenological thinking. Stein’s theses culminate in the characterisation of man as a primarily affected, receiving being. This approach has far-reaching consequences for the world and self-understanding of man and can also be of high relevance to modern phenomenology.